The Role of Badan National Narcotics (BNN) in Conducting Law Enforcement and Drug Users - Yudin Yunus; Siti Alfisyahrin Lasori (Jurnal Hukum Volkgeist, 2021)
Law No. 35 of 2009 on Narcotics in which it is regulated as well as legal sanctions, as well as things that are allowed. The purpose of this study is to understand and understand the implementation of the Role of the National Narcotics Agency (BNN) towards the Implementation of Drug Abuse Rehabilitation in The City of Gorontalo and to find out the Factors That Hinder the Implementation of Rehabilitation of Victims of Narcotics Abuse by the National Narcotics Agency (BNN). This research uses this type of empirical legal research. The results of this study show that the Role of the National Narcotics Agency (BNN) against victims of narcotics abuse by the National Narcotics Agency (BNN) is the first is to prevent, cure, socialize socialization carried out by the city of gorontalo to the community is still very less this is influenced by the budget of the state budget that does not accumulate and factors that hinder the implementation of rehabilitation of victims of narcotics abuse by the National Narcotics Agency (BNN) is harmonization of agencies must be achieved Budget constraints, low role and lack of facilities and infrastructure and lack of socialization. there are things that can hinder others but do not have significant impact as in the factors found if not met will slow the performance of law enforcement. The advice in this study is that the BNN Party maximizes socialization to the community because of the three roles of BNN socialization that has not run optimally and advice for the community and local governments and students can participate in drug eradication to achieve superior human resources.